Implementation of Digital-Based Performance Management at SDN 005 Bukit Timah and SDN 011 Mekar Sari, South Dumai District, Riau - Rudi Fajrin Amin; Priadi Surya (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the implementation of digital-based teacher performance management via the Ruang GTK application on the Rumah Pendidikan digital platform in elementary schools within the South Dumai District. A qualitative approach utilizing a case study method was employed. Data were collected through interviews, observations, and documentation, then analyzed interactively through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that performance management implementation proceeded through stages of planning, execution, monitoring and evaluation, reflection, and the utilization of performance outcomes for teacher professional development. User acceptance of Ruang GTK was generally positive, as the application enhanced administrative efficiency, monitoring capabilities, and data-driven decision-making. Supporting factors included teacher motivation, principal leadership, peer collaboration, learning communities, and the availability of digital devices. Challenges identified included unstable internet connectivity, varying levels of digital literacy, device limitations, system issues, and the need to adapt to changing work cultures. Strategies implemented included continuous mentoring, learning communities, outreach and in-house training, as well as academic and managerial supervision. The study concludes that successful implementation relies on the synergy of technology, leadership, human resources, collaboration, and organizational support.